Hereditary‐like urothelial carcinomas of the upper urinary tract benefit more from adjuvant cisplatin‐based chemotherapy after radical nephroureterectomy than do sporadic tumours. (13th August 2013) - Hollande, Clémence; Colin, Pierre; de, Thibault; Audenet, François; Yates, David R.; Phé, Véronique; Ouzzane, Adil; Droupy, Stéphane; Ruffion, Alain; de, Alexandre; Guy, Laurent; Cussenot, Olivier; et al.
<x xml:space="preserve">Abstract</x> Objective To evaluate the impact of 'hereditary‐like' status in upper tract urothelial carcinoma (UTUC) on the survival of patients who have undergone radical nephroureterectomy (RNU) and adjuvant chemotherapy. Patients and Methods A multicentre retrospective study was performed on all patients with high‐risk UTUC who underwent RNU and adjuvant cisplatin‐based chemotherapy. Using a patient risk identification tool, we distinguished tumours suspected to be hereditary from sporadic tumours and compared survival rates. Results A total of 112 patients with a median age of 67 years were included. Hereditary‐like tumour status was detected in 35 patients (31.3%), while 77 patients (68.7%) had sporadic tumours. The median age was significantly younger in the hereditary‐like tumour group (56.0 vs 69.8 years, P < 0.001). Overall survival (OS) after chemotherapy was significantly better in the group with hereditary‐like tumours than in the group with sporadic tumours (5‐year OS: 48.2 vs 32%; P = 0.008). The cancer‐specific survival (CSS) rate was significantly better in the group with 'hereditary‐like' tumours than in the group with sporadic tumours (5‐year CSS: 58 vs 35%; P = 0.006). Although there was a trend in favour of the hereditary‐like tumours, we observed no significant difference regarding progression‐free survival (PFS) between the two groups (5‐year PFS: 71 vs 52%; P = 0.07). Conclusion Adjuvant chemotherapy after RNU improves survival outcomes in patients with hereditary‐like UTUC compared with those with sporadic tumours.